Foreign bodies in the ear: a simple technique for removal analysed in vitro. Issue 4 (23rd March 2005) - Kumar, S; Kumar, M; Lesser, T; Banhegyi, G
Abstract : Objective: Foreign bodies in the ear are mainly encountered in children. This can often pose a problem especially in an accident and emergency department where a microscope or expert help is not routinely available. This paper presents a simple, safe, and effective way of ear syringing. The ease and simplicity of the procedure along with the equipment are described. Method and result: The equipment consists of a "disposable" sterile kit, consisting of a 20 ml syringe, saline at body temperature and 14 or 16 gauge cannula (without the needle). An in vitro experiment was conducted to calculate the pressure generated by the water jet on the eardrum. The pressure was well below the pressure required to burst a tympanic membrane, and hence this technique is safe to use. Conclusions: Ear syringing is an effective and easy way of removing most foreign bodies. A detailed history and an otoscopic examination must precede the procedure. The novel method of syringing described in this paper with the usual safeguards could be a useful adjunct in the management of this common condition.